Technology in supply chain management and logistics : current practice and future applications - Pagano, Anthony M.; Liotine, Matthew (Elsevier, 2020)
Technology in Supply Chain Management and Logistics: Current Practice and Future Applications analyzes the implications of these technologies in a variety of supply chain settings, including block chain, Internet of Things (IoT), inventory optimization, and medical supply chain. This book outlines how technologies are being utilized for product planning, materials management and inventory, transportation and distribution, workflow, maintenance, the environment, and in health and safety. Readers will gain a better understanding of the implications of these technologies with respect to value creation, operational effectiveness, investment level, technical migration and general industry acceptance. In addition, the book features case studies, providing a real-world look at supply chain technology implementations, their necessary training requirements, and how these new technologies integrate with existing business technologies. Identifies emerging supply chain technologies and trends in technology acceptance and utilization levels across various industry sectorsAssists professionals with technology investment decisions, procurement, best values, and how they can be utilized for logistics operationsFeatures videos showing technology application, including optimization software, cloud computing, mobility, 3D printing, autonomous vehicles, drones and machine learning